Entre narrativas e memórias : viventes nas ruas e a negação do direito à educação (2005-2023) - Sousa, Francismara Gomes de (2023)
The reminiscences of the city about the denial of the right to education, in the light of the narratives of homeless people (HP), weave the threads of memories that unfold in the course of this study. Therefore, the objective is to analyze the impacts of segregations for these non-existent existences in light of official Brazilian data, considering the meanings and significance of education for young and adult individuals living on the streets of João Pessoa, PB. Regarding the methodological approach, Oral History (OH) guides the path of narratives and the production of reflections that point us toward understanding the importance of building emancipatory educational perspectives with and for the street. Along this journey, in addition to oral sources (testimonies and memories), written sources (bibliographic and documentary) and iconographic sources were used. From a Freirean perspective and with the contributions of Benjamin (2013), Le Goff (1990), and Portelli (2016), issues and concerns are discussed, which be presented in this research, also implying the search for alternative Human Rights Education for this historically marginalized population group, with a focus on the resistance processes of urban guerrillas, constrained by exclusions and silencing. The study points us to the relevance of problematizing and understanding inhabiting, existing, and resisting in urban spaces.